ANALISIS PENDAPATAN USAHATANI KAKAO DI DESA LAMBUNU UTARA KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MOUTONG - Purwanto, Andrias Ari; Hadayani, Hadayani; Amtira, Ross M. Olva (AGROTEKBIS, 2019)
This study aims to analyze the income of cocoa business in North Lambunu Village, Parigi Moutong Regency. The study was conducted from September to November 2017 in North Lambunu Village Bolano Lambunu Sub-District. Samples were taken as many as 32 people from cocoa farming population of 125 people who work on cocoa farming in North Lambunu Village by Simple Random Sampling method. Data analysis used is income analysis. The amount of respondent's income in cocoa farming can be calculated by using the following formula: Π = TR - TC, average production of 871Kg/Ha/Year, average selling price of Rp. 23.000 /Kg, obtained the average revenue of Rp.20.030.738/Ha/Year and production cost Rp.7.308.167/Ha/Year. The average income of respondents from cocoa farming in North Lambunu is Rp.12.722.571/ Ha/Year.